2022
DOI: 10.1111/ppc.13092
|View full text |Cite
|
Sign up to set email alerts
|

Predicting work performance and life satisfaction of nurses and physicians: The mediating role of social capital on self‐efficacy and psychological resilience

Abstract: To examine the mediating role of social capital in the effects of selfefficacy and psychological resilience on nurses' and physicians' work performance and life satisfaction. Design and Methods:In this cross-sectional study, data were collected using an online questionnaire.Findings: Social capital had 0.04 indirect effects of general self-efficacy and psychological resilience on work performance, and accounted for 48% and 35% of the total effect, respectively. Social capital had 0.11 and 0.07 indirect effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Extensive research proved that resilience was a major protective factor in the face of challenges or stressors and that people with higher resilience were less vulnerable to prolonged psychological distress induced by negative events (Blanc et al, 2016;Wingo et al, 2017;Ran et al, 2020;Song et al, 2021). Moreover, growing evidence suggested that resilience might have a positive effect on job performance (Hou et al, 2020;Hosgor and Yaman, 2022;Kuşcu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research proved that resilience was a major protective factor in the face of challenges or stressors and that people with higher resilience were less vulnerable to prolonged psychological distress induced by negative events (Blanc et al, 2016;Wingo et al, 2017;Ran et al, 2020;Song et al, 2021). Moreover, growing evidence suggested that resilience might have a positive effect on job performance (Hou et al, 2020;Hosgor and Yaman, 2022;Kuşcu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Life satisfaction derives from the interactive and cumulative contribution of different factors [49]. Several studies have related life satisfaction to self-efficacy in adults [50,51] but also to career adaptability among adults [52], adolescents [53], and in specific groups [54]. A literature review consistently found significant relationships between life satisfaction and sociodemographic variables (e.g., age, gender, ethnicity, socioeconomic status), personality, risk behaviors (e.g., drug, alcohol, and tobacco use), and family environment (e.g., parenting styles, family violence) [55].…”
Section: Life Satisfactionmentioning
confidence: 99%
“…The direct effect of SE, in the model, indicates the immediate influence that workers' beliefs in their own capabilities have on their levels of JS and LS. Higher levels of SE tend to lead to increased JS, as doctors who possess a strong belief in their abilities are more likely to feel competent and successful in their work (Karatepe et al ., 2022). Similarly, SE positively impacts LS, as doctors with a strong sense of SE tend to have a greater confidence and perceived control over their lives, which leads to higher overall LS.…”
Section: Hypotheses Developmentmentioning
confidence: 99%